Analisis Digital Forensik Recovery Data pada Flashdisk Menggunakan Metode National Institute Of Justice (NIJ) - Huda, Syaiful; Novrianda Dasmen, Rahmat; Ardiansyah, Ardiansyah; Pranata, Viren; Januarta, Ari (JURNAL ILMIAH INFORMATIKA, 2024)
Investigation of the application of computer forensic techniques in the process of returning data by utilizing one of the tools namely disk tests In this context, focus is given to the analysis of the performance and effectiveness of forensic tools used to restore data from digital storage media, especially at the stage of disk test l. In IT forensics can be found evidence such as documents, financial information, e-mail, logs, videos, voice mail transcriptions and others as Especially in documents or data that have been deliberately taken or deleted data from USB devices and must be recovered data that has been lost In the early stages of research the author will collect data on the tools used and therefore, The author considers that tools are needed that can analyze which tools are better and more efficient in dealing with one of these problems. Tools to be used are Teskdisk. The results of this study provide deep insight into the effectiveness of the tesk disk tool in the context of data recovery through a computer forensic approach. The implications of these research findings can support the development of best practices in dealing with the challenges and complexities of data returns in an evolving digital world.